2022
DOI: 10.1001/jamaophthalmol.2022.3988
|View full text |Cite
|
Sign up to set email alerts
|

The Male to Female Ratio in Treatment-Warranted Retinopathy of Prematurity

Abstract: ImportanceLiterature and anecdotal evidence suggest a relationship between male sex and retinopathy of prematurity (ROP). It is not known whether a difference, if present, is sex-related pathophysiologic predisposition or sex difference in meeting ROP screening criteria.ObjectiveTo evaluate the association of sex with the development of treatment-warranted ROP.Data SourcesPubMed, Embase, and Web of Science databases were searched from 2000 to 2022. The search strategy used keywords including retinopathy of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 141 publications
1
4
0
Order By: Relevance
“…To our knowledge, this is the most comprehensive meta-analysis to date on sex differences in the development of ROP. Our data confirm the previous observations that the more severe forms of ROP are more common in preterm boys than in preterm girls [ 9 ]. However, when the study focused on any ROP, we did not observe sex differences.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To our knowledge, this is the most comprehensive meta-analysis to date on sex differences in the development of ROP. Our data confirm the previous observations that the more severe forms of ROP are more common in preterm boys than in preterm girls [ 9 ]. However, when the study focused on any ROP, we did not observe sex differences.…”
Section: Discussionsupporting
confidence: 92%
“…Very recently, Bahmani et al conducted a meta-analysis of risk factors for any ROP and found no sex differences when they pooled the 121 studies that reported these data [ 8 ]. In addition, Hoyek et al performed a meta-analysis of the male-to-female ratio in preterm infants requiring treatment for ROP [ 9 ]. They included 316 studies and found that a higher percentage of boys than girls were screened and treated for ROP [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm birth and postpartum oxygen therapy have been reported to be closely related to the occurrence of ROP, but many studies have proposed that the pathogenesis of ROP may exist in utero , and the prenatal intrauterine environment may be related to the occurrence of severe ROP ( 30 , 31 ), including maternal preeclampsia ( 32 ), chorioamnionitis ( 33 ), and smoking ( 34 ). In addition, gender has also been shown to be associated with the occurrence of severe ROP ( 35 ). At present, there are conflicting reports about the relationship between PROM and ROP.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of retinopathy of prematurity among infants born between 22 and 28 weeks gestational age remains 12.8% ( 69 ). Males are more likely to be screened for Retinopathy of Prematurity (ROP), and a higher percentage of male infants are treated for ROP as compared to female infants (55%, 95% CI: 52–58%) ( 43 ). Males are also at higher risk of having severe ROP (RR: 1.14, 95% CI: 1.07–1.22) ( 36 , 44 ), suggesting that males are at higher risk of progression of ROP.…”
Section: Part I Sex Differences In Neonatal Outcomesmentioning
confidence: 99%